Thermal comfort analyses of the old mosque in a humid climate a case study on old mosque Gunong Kleng, Aceh Barat, Indonesia/ Teuku Muhammad Al Aiyubi, Laina Hilma Sari and Safwan - Al Aiyubi, Teuku Muhammad; Sari, Laina Hilma; Safwan, Safwan (Universiti Teknologi MARA, Perak, 2024)
Old mosques have a typology that reflects the traditions and culture of the community which has local wisdom values. Indonesia has a tropical climate that influences aspects of life, one of which is the shape of buildings that adapt to natural conditions. The Old Mosque Gunong Kleng is a historic and oldest mosque in West Aceh Regency, Indonesia, which was built in 1927. This research aims to identify the effect of openings on thermal comfort and evaluate the thermal comfort felt by visitors to the Tuha Gunong Kleng Mosque. This research uses quantitative methods by collecting data from questionnaires using the Thermal Sensation Vote (TSV) method as well as field measurements consisting of air temperature, humidity, and air velocity. The measuring instruments used were the USB Data Logger, Anemometer, and Weather Station. The results of this research were then compared with the effective temperature of SNI 036572-2001. The results of field measurements of air temperature variables do not comply with comfort standards, in contrast to wind speed and humidity. However, this is inversely proportional to the perception of respondents who can accept the thermal environment.